Parental Empathy as a Dual-Process Regulatory Mechanism in Early Caregiving: A Systematic Review - Srikandi, Putri Gevi; Kurniawati, Farida; Suharso, Puji Lestari (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – Parental empathy is widely treated as a protective resource in early caregiving, yet the literature remains theoretically fragmented and methodologically heterogeneous, limiting a clear explanation of how empathy shapes caregiving quality and child development. This review addresses that gap by examining parental empathy as a dual-process regulatory mechanism rather than a uniformly beneficial parental trait.Design/methods/approach – A systematic literature review following PRISMA 2020 was conducted across ProQuest, Taylor & Francis Online, ScienceDirect, and APA PsycNet. Twenty-six peer-reviewed empirical studies published between 2015 and 2025 were synthesized thematically to identify recurrent patterns in how parental empathy operates across caregiving contexts.Findings – The review indicates that parental empathy operates through two distinct pathways. other-oriented empathic concern supports attuned, responsive, and developmentally supportive caregiving, whereas empathic distress weakens parental regulatory capacity and is associated with reactive parenting, heightened stress, and less adaptive child outcomes. Across the evidence base, the developmental significance of empathy depended less on empathic feeling alone than on parents’ ability to remain emotionally engaged without becoming dysregulated.Research implications/limitations – The review integrates psychological, developmental, intervention, and neurobiological evidence, but most included studies were conducted in Western contexts and relied heavily on self-report measures. The synthesis was also conducted by a single reviewer, which may limit interpretive breadth.Practical implications – Parenting interventions should move beyond promoting empathy in general and instead strengthen emotional regulation under caregiving stress. Programs are likely to be more effective when they explicitly distinguish empathic concern from empathic distress and treat that distinction as a practical target of intervention design.Originality/value – This review reconceptualizes parental empathy as a dual-process regulatory mechanism in early caregiving. By distinguishing regulated concern from dysregulated distress, it extends existing empathy theory into the parenting domain and provides a more precise conceptual basis for research and intervention, particularly in underexamined non-Western and developing -country contexts where caregiving strain may intensify empathic distress.Paper type Systematic literature review